DNA sequencing confirms the involvement of Leishmania (L.) amazonensis in american tegumentary leishmaniasis in the state of São Paulo, Brazil (Clinics, 2008)
INTRODUCTION: American tegumentary leishmaniasis (ATL) represents one of the most important public health issues in the world. An increased number of autochthonous cases of ATL in the Northeastern region of São Paulo State has been documented in the last few years, leading to a desire to determine the Leishmania species implicated. METHODS: PCR followed by DNA sequencing was carried out to identify a 120bp fragment from the universal kDNA minicircle of the genus Leishmania in 61 skin or mucosal biopsies from patients with ATL. RESULTS: DNA sequencing permitted the identification of a particular 15bp fragment (5' GTC TTT GGG GCA AGT... 3') in all samples. Analysis by the neighbor-joining method showed the occurrence of two distinct groups related to the genus Viannia (V) and Leishmania (L), each with two subgroups. Autochthonous cases with identity to a special Leishmania sequence not referenced in Genbank predominated in subgroup V.1, suggesting the possible existence of a subtype or mutation of Leishmania Viannia in this region. In the subgroup L.2, which showed identity with a known sequence of L. (L.) amazonensis, there was a balanced distribution of autochthonous and non-autochthonous cases, including the mucosal and mucocutaneus forms in four patients. The last observation may direct us to new concepts, since the mucosal compromising has commonly been attributed to L. (V.) braziliensis, even though L. (L.) amazonensis is more frequent in the Amazonian region. CONCLUSIONS: These results confirm the pattern of distribution and possible mutations of these species, as well as the change in the clinical form presentation of ATL in the São Paulo State.